P. 1
1_5

# 1_5

|Views: 1|Likes:

### Availability:

See more
See less

07/30/2014

pdf

text

original

Let

2

Y X

=

.

a) If ( )

( )

X

i

f x

x i

6

1

1
6

=

=

∑ δ

, find ( )
Yf y.

b) If ( )

( )

X

i

f x

x i

3

2

1
6

= −

=

∑ δ

, find ( )
Yf y.

a) If X takes the values (

)

1,2,.......,6 with probability of 1

6, then Y takes the

values 2

2

2

1,2,.......,6 with probability 1

6. That is, ( )

( )

Y

i

f y

x i

6

2

1

1
6 =

= δ −

.

b) If, however, X takes the values 2,1,0,1,2,3

− −

with probability 1

6, then

Y takes the values 0,1,4,9 with probabilities 1111

,,,
6336 respectively.

That is,

( )

( ) ( )

( ) ( )

1

1

9

1

4

6

3

Yf y

y y

y

y

⎤ ⎡

= δ + δ − + δ − + δ −

⎦ ⎣

2.4.2 Functions of two random variables

Given two random variables X and Y (assumed to be continuous type),

two new random variables, Z and W are defined using the transformation

( )

,

Z g X Y

=

and

( )

,

W h X Y

=

Principles of Communication Prof. V. Venkata Rao

2.38

Given the above transformation and

( )

,

,

X Y

f x y, we would like to obtain

( )

,

,

Z W

f z w. For this, we require the Jacobian of the transformation, denoted

,
,

z w

J

x y

⎛ ⎞
⎜ ⎟
⎝ ⎠ where

,
,

z z
x y

z w

J

x y

w w
x y

∂ ∂
∂ ∂

⎛ ⎞

=

⎜ ⎟

∂ ∂

⎝ ⎠

∂ ∂

z w z w
x y y x

∂ ∂ ∂ ∂

=

∂ ∂ ∂ ∂

That is, the Jacobian is the determinant of the appropriate partial derivatives. We

shall now state the theorem which relates

( )

,

,

Z W

f z w and

( )

,

,

X Y

f x y.

We shall assume that the transformation is one-to-one. That is, given

( )

1

,

g x y z

=

,

(2.33a)

( )

1

,

h x y w

=

,

(2.33b)

then there is a unique set of numbers, ( )

1

1

,

x y satisfying Eq. 2.33.

Theorem 2.2: To obtain

( )

,

,

Z W

f z w, solve the system of equations

( )

1

,

g x y z

=

,

( )

h x y w1

, =

,

for x and y. Let ( )

1

1

,

x y be the result of the solution. Then,

( ) ( )

,

1

1

,

1

1

,

,

,
,

X Y

Z W

f x y

f z w

z w

J

x y

=

⎛ ⎞
⎜ ⎟
⎝ ⎠

(2.34)

Proof of this theorem is given in appendix A2.1. For a more general version of

this theorem, refer [1].

Principles of Communication Prof. V. Venkata Rao